SKA1/2/3 is a biomarker of poor prognosis in human hepatocellular carcinoma - Song, Guo-Qiang; He, Tian-Li; Ji, Ke-Jie; Duan, Yi-Meng; Zhang, Jia-Wen; Hu, Guo-Qiang (Frontiers in Oncology, 2022)
Spindle and kinetochore-associated complex subunits 1–3 (SKA1–3) stabilize the kinetochore-attached spindle microtubules in metaphase. SKA1–3 are dysregulated in several cancers and can be used to predict the prognosis of patients. However, the potential clinical applications of SKA1–3, particularly in hepatocellular carcinoma (HCC) prognosis and progression, have not been fully elucidated.